O Conselho Supremo Militar e de Justiça como órgão do sistema judiciário militar do Império (1808-1869) - Neves, Getulio Marcos Pereira (2023)
This thesis has as its goal the analysis of the formation and consolidation of the military forum in Brasil. Henceforth, the thesis has as its main focus the Supreme Council, both Military and of Justice, as the body that serves the analysis of the military judiciary system of the Brazilian Empire. Its main object of analysis is the relationship between contemporary political conditions and the way the structure established and worked from its very beginnings until the full consolidation of its assignments. The thesis focuses on the examination of such political oscillations and their consequences over the deliberations by the tribunals revisional activity, at a point in time when the juridic framework and judicial structure was still taking shape in this new nation. The empirical basis to this thesis samples trial records given between 1859-1869 collected from the archive of the Superior Military Tribunal.